2013
DOI: 10.1088/0264-9381/30/23/235009
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulations of the LARES space experiment to test General Relativity and fundamental physics

Abstract: Abstract. The LARES (LAser RElativity Satellite) satellite was successfully launched in February 2012. The LARES space experiment is based on the orbital determinations of the laser ranged satellites LARES, LAGEOS (LAser GEOdynamics Satellite) and LAGEOS 2 together with the determination of the Earth's gravity field by the GRACE (Gravity Recovery And Climate Experiment) mission. It will test some fundamental physics predictions and provide accurate measurements of the framedragging effect predicted by Einstein… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 32 publications
0
52
0
Order By: Relevance
“…Those tripled errors were then propagated to the nodes of the three satellites of the LARES experiment providing a systematic error of about 0.04 in frame-dragging caused by the uncertainties in the knowledge of the Earth's gravity field even zonal harmonics. Previous error analyses [5], [18]- [27] have shown that the systematic errors associated with all the other perturbations, i.e. tides, non-gravitational perturbations and other unidentified effects, amount to about 0.03.…”
Section: Lares Frame-dragging Missionmentioning
confidence: 94%
“…Those tripled errors were then propagated to the nodes of the three satellites of the LARES experiment providing a systematic error of about 0.04 in frame-dragging caused by the uncertainties in the knowledge of the Earth's gravity field even zonal harmonics. Previous error analyses [5], [18]- [27] have shown that the systematic errors associated with all the other perturbations, i.e. tides, non-gravitational perturbations and other unidentified effects, amount to about 0.03.…”
Section: Lares Frame-dragging Missionmentioning
confidence: 94%
“…Here, I lists the major issues which, in my opinion, affect [15] In the sensitivity analysis leading to the choice of the most potentially hazardous parameters to be considered, Ciufolini et al [15] consider only the first five even zonals, despite it was pointed out in several papers that also those of degree as high as ℓ $ 50-70 may be of relevance because of the lower altitude of LARES with respect to the Lageos satellites. Ciufolini et al [15] base their choice on previous papers of them in which this issue was treated insufficiently.…”
Section: My Analysismentioning
confidence: 99%
“…Ciufolini et al [17] analyzed the first 105 days of LARES; a critical analysis of their results is offered in [67]. Recently, Ciufolini et al [15] performed a set of Monte Carlo simulations to strengthen their conclusions: they are the subject of the following discussion.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these measurements have confirmed the frame dragging effect, but they have not yet reached the full resolution that would put GR and other fundamental theories to a test 4 . In order to provide tests of fundamental physics (GR, Horava-Lifshitz or Chern-Simons theories of gravity, etc.…”
Section: Introductionmentioning
confidence: 98%